Reinterpretation of Minangkabau Boys’ Merantau Culture in Dance Creation - Fattahul Anugraha; Ariefin Alham Jaya Putra; Syahril Syahril; Zulfikar Rizki Ananda; Suaida Suaida (Pascasarjana Institut Seni Indonesia Padang Panjang, 2026)
This article discusses the creation process of the dance work Budaya Merantau, which originates from the socio-cultural phenomenon of migration in Minangkabau society. The study focuses on how the surau, as a space for religious education, customary learning, martial arts practice, and character formation among Minangkabau boys, is reinterpreted as a conceptual foundation for dance creation. The main issue addressed is how migration patterns expressed in Minangkabau proverbs and oral philosophy can be transformed into a choreographic method. This study employs a research-based creation method involving observation, interviews, literature review, documentation, data analysis, movement exploration, exploration of space-time-energy, property experimentation, rehearsal, and performance. The creation process reveals that the pattern of merantau can be structured into three dramatic parts: the encouragement to migrate, the ability to socialize and adapt in a new environment, and the longing for the homeland. These structures are embodied through movements derived from Minangkabau pencak silat, everyday gestures, shifting floor patterns, the use of sarong and white fabric, Minangkabau musical idioms, and religious expressions associated with the memory of the surau. The article argues that merantau can be understood not only as social mobility but also as a creative method for producing contemporary dance based on tradition.